1997
DOI: 10.1063/1.366479
|View full text |Cite
|
Sign up to set email alerts
|

Performance of heterojunction p+ microcrystalline silicon n crystalline silicon solar cells

Abstract: We have studied by Raman spectroscopy and electro-optical characterization the properties of thin boron doped microcrystalline silicon layers deposited by plasma enhanced chemical vapor deposition ͑PECVD͒ on crystalline silicon wafers and on amorphous silicon buffer layers. Thin 20-30 nm p ϩ c-Si:H layers with a considerably large crystalline volume fraction (ϳ22%) and good window properties were deposited on crystalline silicon under moderate PECVD conditions. The performance of heterojunction solar cells inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…Tested alternatives to replace the a-Si:H stacks are (microcrystalline) silicon oxides [136,137,182,183] and carbides [148,[184][185][186]. Microcrystalline silicon has a lower but indirect bandgap and features a higher doping efficiency, making it an attractive material for emitter [52,[187][188][189][190] and BSF formation [189,[191][192][193] as well. Of note is that such films may also resolve possible contact problems between TCO-layers and doped films [192,194].…”
Section: Future Directionsmentioning
confidence: 99%
“…Tested alternatives to replace the a-Si:H stacks are (microcrystalline) silicon oxides [136,137,182,183] and carbides [148,[184][185][186]. Microcrystalline silicon has a lower but indirect bandgap and features a higher doping efficiency, making it an attractive material for emitter [52,[187][188][189][190] and BSF formation [189,[191][192][193] as well. Of note is that such films may also resolve possible contact problems between TCO-layers and doped films [192,194].…”
Section: Future Directionsmentioning
confidence: 99%
“…This effect has been attributed to better properties of an a-Si:H(i)/c-Si interface, compared with an a-Si:H(doped)/c-Si interface [2,11,12].…”
Section: Resultsmentioning
confidence: 99%
“…So far, a number of studies have reported the improvement of a-Si:H/c-Si cell performance by the incorporation of a-Si:H i-layer at the a-Si:H/c-Si heterointerface [2,11,12]. This effect has been attributed to better properties of an a-Si:H(i)/c-Si interface, compared with an a-Si:H(doped)/c-Si interface [2,11,12].…”
Section: Resultsmentioning
confidence: 99%
“…Particular treatments of the crystalline surface have been investigated, such as wet cleaning by HF solutions [4] passivation by hydrogen [1,2], dry cleaning by plasmas of CF 4 [5] and CF 4 +O 2 [6], and the use of a microcrystalline (lc) [3], or a-Si:H [1] thin layer as a buffer layers to improve the interface with the c-Si substrate.…”
Section: Introductionmentioning
confidence: 99%